Pengembangan Media Interaktif Berbantuan Canva Pada Pembelajaran IPA Dengan Pendekatan Saintifik - Siti Nurhalisa, Sukmawarti (Pusdikra Publishing, 2022)
This development aims to develop Canva-assisted products for science learning with a scientific approach. Due to the current condition, namely the Covid-19 virus, this research was carried out in the library of the Muslim Nusantara University Al Washliyah in accordance with the rector's circular letter Number: 040/BAA-UMNAW/A.16/2020, namely conducting a literature review. And follow the rules made in the UMN Al Washliyah library. The research only takes data that is the same as the title of this thesis, data that has been obtained in a library or journal with a total of 3 journlas. Based on the results of the development, this development went through 3 stages, namely define, design, and development. Then it is validated by material and media experts as a result of material and media experts that the product developed is feasible.